Diferenciación en servicio para el sector de grasas y aceites vegetales en Colombia, haciendo uso de metodologías de innovación - Solís Rodríguez, Claudia Catalina (Universidad Antonio Nariño, 2023)
This article demostrates that methodology of service design innovation the fats and vegetable oils sector, explains why service differentiation of critical importance and how it can the reason why to achieved through innovation. It methodologies to a large Colombian company in the industrys, and the result was a service model that can be generalised to de rest of the industry, and possibly beyond it.